A configuration of sustainable sourcing and supply management strategies. Issue 2 (March 2017) - Akhavan, Roya Manuela; Beckmann, Markus
Abstract: This paper seeks to analyze empirical differences and patterns in applied sustainable sourcing and supply management (SustSSM) strategies. The question is whether companies employ individual SustSSM practices in reoccurring configurations. The study aims to identify such typical corporate SustSSM approaches and how they vary across contingency factors such as industry or region. We employed a two-step methodology. First, a literature review derives scoring scales for six categories of how companies can integrate sustainability into sourcing. Second, using these scales for a content analysis of sustainability reports from 99 corporations spread across different regions, a taxonomy is derived by means of a cluster analysis. Identifying five corporate types of how firms configure their SustSSM strategy, the analysis suggests that companies do not combine SustSSM practices randomly. Rather, individual SustSSM practices are combined to alternative configurations that follow different logics to form sustainable sourcing strategies. Addressing a cross-regional and cross-industry sample, the results encourage further investigating the interplay of different SustSSM practices. In doing so, we show the need to align SustSSM configurations with a firm's specific operative supply chain structures and strategic goals. Highlights: Companies combine individual sourcing practices to recognizable configurations. The configuration approach is applied to identify sustainable sourcing strategies. To secure sustainability compliance companies prioritize collaborative initiatives.